The application of alkaline and acidic electrolyzed water in the sterilization of chicken breasts and beef liver. Issue 3 (1st November 2015) - Shimamura, Yuko; Shinke, Momoka; Hiraishi, Miki; Tsuchiya, Yusuke; Masuda, Shuichi
Abstract: The sterilization effect of a combination treatment with alkaline electrolyzed water (AlEW) and strong acidic electrolyzed water (StAEW) on fresh chicken breasts and beef liver was evaluated. Samples (1, 5, and 10 g) were inoculated with Salmonella Enteritidis NBRC3313, Escherichia coli ATCC 10798, Staphylococcus aureus FDA209P, and S. aureus C‐29 [staphylococcal enterotoxin A (SEA) productive strain] and subjected to a dipping combination treatment (4°C and 25°C for 3 min) with AlEW and StAEW. Combination treatment with AlEW and StAEW significantly reduced the bacteria, and reduction of more than 1 log colony‐forming units (CFU)/g was achieved. Furthermore, this combination treatment significantly decreased the SEA gene expression level in samples. Some quality variables of the meat samples such as pH, lipid oxidation, color, amino‐acid content, texture, and sensory characteristics showed no significant differences between the combination treatment with AlEW and StAEW and the untreated control. Abstract : The experimental findings suggest that combination treatments with alkaline electrolyzed water and strong acidic electrolyzed water extended the shelf life of chicken meat and beef liver without changing some quality variables of the meat.